1988
DOI: 10.1056/nejm198801073180102
|View full text |Cite
|
Sign up to set email alerts
|

Renal Disease in Type I Glycogen Storage Disease

Abstract: Although kidney enlargement occurs in Type I glycogen storage disease, renal disease has not been considered a major problem. Death from renal failure in three patients known to us prompted a study of renal function in this disorder. Of the 38 patients with Type I glycogen storage disease under our care, the 18 children under 10 years old had normal renal function. Fourteen of the 20 older patients (13 to 47 years) had disturbed renal function, manifested by persistent proteinuria; many also had hypertension, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
3
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(100 citation statements)
references
References 16 publications
3
92
3
2
Order By: Relevance
“…Renal biopsies performed in three GSD I patients with persistent proteinuria showed focal segmental glomerulosclerosis (11). These findings might suggest an etiology of glomerular hyperfiltration and proteinuria similar to diabetic nephropathy (12).…”
mentioning
confidence: 69%
“…Renal biopsies performed in three GSD I patients with persistent proteinuria showed focal segmental glomerulosclerosis (11). These findings might suggest an etiology of glomerular hyperfiltration and proteinuria similar to diabetic nephropathy (12).…”
mentioning
confidence: 69%
“…There are several case reports 3,4 and researches 5,6,7 which reveal that in type 1 GSD hypercalciuria and hypocitricaciduria increase with age and dRTA has been implicated in development of nephrolithiasis 8 and chronic renal disease. There are several case reports of GSD type 1 patients later presenting with renal stones who are found to have dRTA 3,4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies concluded that citrate supplementation may be beneficial in preventing or ameliorating nephrocalcinosis and development of urinary calculi in GSD 1a 6 . One study states that chronic renal disease is a frequent and potentially serious complication of type 1 GSD and physicians should monitor renal function carefully in patients with this disorder 7 . But there were no reported cases of GSD type 1 initially presenting with dRTA.…”
Section: Discussionmentioning
confidence: 99%
“…Parece que um considerável número de pacientes, após um período de hiperfiltração renal silenciosa, desenvolve danos renais com proteinúria, hipertensão e disfunção renal subseqüente. Na biópsia renal encontra-se glomeruloesclerose focal, com a intensidade da fibrose proporcional ao grau de insuficiência renal [22][23][24] .…”
Section: Complicações Renaisunclassified